A New Perspective on the Development of Culture and Art - Akhimbetova Gulbahar Qanatbaevna; Munteeva Gulnara Uzaqbaevna (Research Parks Publishing LLC, 2022)
In the process of historical reforms in the area of culture and art in New Uzbekistan, the essay discusses the relevance of the stages of growth of national culture and development of national values.